J-Curve of Productivity and Growth : Indian Manufacturing Post-Liberalization - Virmani, Arvind (IMF Working Papers; Working Paper, 2011)
Most estimates of Indian manufacturing productivity find a slowdown in the 1990s. This has puzzled analysts, given that 1990s reforms were deeper and wider than the 1980s reforms that raised the growth rate of the Indian economy by 2 per cent points. This paper tests the hypothesis of the J curve of Productivity and Growth following major liberalization and finds it to be broadly supported by the data: Technological obsolescence, gradual adoption of new technology and learning by doing result in negative effects on measured productivity.